Cyclotella or Discostella? An Evaluation of the Morphological and Molecular Evidence Regarding the Generic Placement of a Centric Diatom from Eastern Asia and the Creation of Discocyclus gen. nov. - Patrick Rioual; Konrad Schultz; Gyeongje Joh; Mengna Liao (Taxonomy)
In this study on diatoms, which are unicellular microalgae with a siliceous cell wall, images obtained by electron microscopy were used to compare three taxa from East Asia that were referred as Cyclotella hubeiana, Discostella guiyangensis and “Cyclotella fottii” in the original studies. Morphometrical and morphological analyses indicate that these three taxa are conspecific. The distinctive morphological features of this species are the following: one rimoportula located on the valve mantle within the ring of marginal fultoportulae, marginal fultoportulae situated on costae with internally two satellite pores positioned circumferentially (laterally) and externally long tubular opening, biseriate striae and branching costae. A comparison of these morphological features with those of Discostella and Cyclotella species and a re-assessment of the existing molecular data suggest that this species could be separated from both these genera. On this basis, we describe the new genus Discocyclus gen. nov. with Discocyclus hubeianus comb. nov. as the type species.